Promoting professionalism via a video‐based educational workshop for academic hospitalists and housestaff. Issue 7 (18th June 2013) - Farnan, Jeanne M.; O'Leary, Kevin J.; Didwania, Aashish; Icayan, Liza; Saathoff, Mark; Bellam, Shashi; Anderson, Andy; Reddy, Shalini; Humphrey, Holly J.; Wayne, Diane B.; Arora, Vineet M.
Abstract : BACKGROUND: Unprofessional behavior can compromise care and detract from the hospital learning environment. Discrepancy between professional behaviors formally taught and what is witnessed has become increasingly evident. METHODS: With funding from the American Board of Internal Medicine Foundation, a workshop was developed to address unprofessional behaviors related to inpatient care previously identified in a multi‐institution survey. The aims were to utilize video‐based education to illustrate unprofessional behaviors, how faculty play a role in promoting such behaviors, and facilitate reflection regarding motivation for and prevention of these behaviors. Hospitalists and housestaff at 3 Chicago‐area academic hospitals and 1 community teaching affiliate participated. Videos were debriefed, identifying barriers to professional behavior and improvement strategies. A postworkshop survey assessed beliefs on behaviors and intent to change practice. RESULTS: Forty‐four (53%) faculty and 244 (68%) residents (postgraduate year 1 and greater) participated. The workshop was well received, with 89% reporting it "useful and effective." Two‐thirds expressed intent to change behavior. Most (86%) believed videos were realistic and effective. Those who perceived videos as "very realistic" were more likely to report intent to change behavior (93% vs 53%, P = 0.01). CONCLUSIONS: Video‐based education is a feasible way to promote reflection and address unprofessional behaviors among providers and may positively impact the learning environment. Journal of Hospital Medicine 2013;8:386–389. © 2013 Society of Hospital Medicine